Dopuszczalność skargi kasacyjnej w postępowaniu cywilnym: Admissibility of extraordinary appeal complaint in civil proceeding - Krawczyk, Michał (Management and Administration Journal, 2021)
The article presents, in foothold about newest jurisdiction of Highest Court, questions related with admissibility of extraordinary appeal complaint in civil proceedings.